Clinical respiratory medicine - Spiro, Stephen G; Silvestri, Gerard A; Agustí, Alvar (Elsevier Saunders, 2012)
Clinical Respiratory Medicine provides practical guidance to help you more effectively diagnose and manage the full range of pulmonary disorders, including those seen in today's most challenging patient populations. Now with over 400 brand-new review questions and 25 videos available online, this medical reference book delivers all of the answers you need to ensure the best outcomes.Better manage and treat patients with pulmonary disease with complete clinical coverage of the critical information relevant to your everyday practice, presented in a templated, user-friendly format. Find critical information quickly with the help of diagnostic algorithms. Test your knowledge of respiratory medicine with the help of 400 brand-new review questions.Watch and learn. Over 25 videos of practical procedures are available online at www.expertconsult.com.Thoroughly understand the needs and recognize co-morbidities of particular patient populations through entirely new chapters on lung structure, echocardiography, and obesity and its effects.Access the latest research and advancements in lung cancer, benign tumors, and the importance of pulmonary physiology in understanding lung function and the disease processes that occur.Take a practical approach to the diagnosis and management of patients with respiratory disorders using this ideal source for reference in clinical practice